Knowledge attitudes and practices about diabetes and diabetic retinopathy among diabetic retinopathy patients at a tertiary care hospital in Goa - Raiturcar, Tanvi Poy; Sawant, Apika K.; Lotliker, Shreya S.; Cacodcar, Jagadish A.; Vernekar, Preksha P. (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetic retinopathy is one of the most common complication of diabetes with a prevalence of 7.3-25%. There have been several studies done in India to assess the knowledge and awareness on diabetes and diabetic retinopathy among patients with diabetes, however very few studies assessed knowledge, awareness and practices amongst patients with diabetic retinopathy.4-7 Besides, no such study was undertaken at Goa Medical College. Methods: A cross-sectional study was conducted among 100 consecutive diabetic retinopathy patients attending ophthalmology out-patient department (OPD) at Goa Medical College and Hospital. The patients were administered a pre-tested proforma to assess their level of awareness and attitudes and practices towards diabetes and diabetic retinopathy. Data was entered in Microsoft excel 2010; analysed using the SPSS version 22. Chi-square test was used as test of significance. Results: In our study, 58% were aware of the symptoms of diabetes. 15% were aware of the multiple complications. 35% had knowledge about only one test for detecting diabetes i.e. fasting blood sugar level. 22% had never heard about HbA1c. 49% were not aware that they had diabetic retinopathy. 76% felt it is important to continue medications even if blood sugar levels were normal. 62% were aware of the importance of exercise. 71% took their medications regularly, 72% checked their blood sugar regularly. There was a significant association between educational status and awareness and practices towards diabetes. Conclusions: The diabetic retinopathy patients in our study had a fair knowledge about diabetes and diabetic retinopathy.